COP27 Climate Change Conference: Urgent Action Needed for Africa and the World - Chris Zielinski, (AlQalam Journal of Medical and Applied Sciences, 2022)
The 2022 report of the Intergovernmental Panel on Climate Change (IPCC) paints a dark picture of the future of life on earth, characterised by ecosystem collapse, species extinction, and climate hazards such as heatwaves and floods [1]. These are all linked to physical and mental health problems, with direct and indirect consequences of increased morbidity and mortality. To avoid these catastrophic health effects across all regions of the globe, there is broad agreement—as 231 health journals argued together in 2021—that the rise in global temperature must be limited to less than 1.5oC compared with pre-industrial levels. While the Paris Agreement of 2015 outlines a global action framework that incorporates providing climate finance to developing countries, this support has yet to materialise [2]. COP27 is the fifth Conference of the Parties (COP) to be organised in Africa since its inception in 1995. Ahead of this meeting, we—as health journal editors from across the continent—call for urgent action to ensure it is the COP that finally delivers climate justice for Africa and vulnerable countries. This is essential not just for the health of those countries, but for the health of the whole world. Cite this article. Atwoli L, Erhabor G, Gbakima A, Haileamlak A, Ntumba J, Laybourn-Langton L. COP27 Climate Change Conference: Urgent Action Needed for Africa and the World. Alq J Med App Sci. 2022;5(2):514-516. https://doi.org/10.5281/zenodo.7222080